Análise multicriterial para avaliação da susceptibilidade à ocorrência de quedas de blocos na vertente noroeste da serra da Meruoca, Ceará, Brasil - Adisson Souza Tavares; Frederico de Holanda Bastos (Confins)
Multicriterial analysis techniques assist in making decisions on natural events, using combining variable methods, assigning weights and importance values ​​which influence certain phenomena. Thus, this research aims to develop the susceptibility mapping to the occurrence of block falls in the hydrographic basin of the Poção stream, located in the northwestern slope of the Meruoca massive (Ceará). For this, nine criteria were listed for analysis: slope, rainfall, seismicity, horizontal and vertical curvatures, terrain roughness, structural guidelines, soil use and cover and mass movements scars. Afterwards, a hierarchical analysis was performed to assign weights and, finally, the map legends normalization by the fuzzy logic. From the results it was identified that most of the basin has a very low and low susceptibility level (46%), being these the lower portions close to the exutory already on the erosive surfaces surrounding the massif, in addition to the alveolar plains, with colluvium-alluvial deposit, located on the elevated surfaces of the mountain range. The most susceptible classes, on the other hand, make up about 1/3 of the area, being environments that are not favorable to human occupation, very influenced by the high declivities, preferably located on the massif slopes.